Cassava growth and production under two planting arrangements - Tavora, Francisco José Alves Fernandes; Melo, Francisco Ivaldo Oliveira (Pesquisa Agropecuaria Brasileira, 1993)
A field study was carried out in 1988, in Pacajus, Ceará, Brazil, with the objective of studying the effects of planting arrangement and row orientation on the production of two cassava (Manihot esculenta) cultivars. The cultivar Jaburu showed higher ability for fresh weight accumulation in roots and shoots between 90 and 190 days after planting. Cv. Saracura had higher plants, with higher number of apices, branches, leaves and tuberous roots, thicker canopy and smaller roots. Planting arrangement had no significant effect on the following parameters: root length and diameter; number of leaves; leaf area index; plant height; canopy width; number of apices; shoot fresh weight and harvest index. The number of roots and the root yield were significantly affected by planting arrangement, with single row outyielding double row arrangement. Planting arrangement had no effects on light attenuation by plants.